Push Factors, Household Support and Effects of Communal Land Distribution in Gozamin Distric, Ethiopia - Derseh, Ermiyas; Belay, Mehretie (Ethiopian Journal of Social Sciences, 2019)
Nowadays, communal land distribution (CLD) in Ethiopia causes complaints in rural areas. This study describes the push factors, household support and effects of CLD in Gozamin district, Ethiopia. Data were gathered using questionnaires, focus groups, interviews and observations. Descriptive and inferential statistics were used in data analysis. Youth unemployment, farmland shortage, land laws, illegal encroachments and awareness gaps were identified as main drivers of CLD. Support to CLD was found significantly differing with sex, age, farmland, livestock, income and dependency levels of household groups. Youth employment opportunity was the positive effect of CLDs. Rising farmer conflicts, contraction of indigenous wildlife and grazing pastures, decline of livestock products and tenure insecurity were adverse impacts of CLDs. It is suggested that land laws promoting CLD be revised to reduce encroachments and conflicts. Alternative employment, livestock feeding and fuel options should be introduced to minimize farmland shortages and the pressure on communal resources.Â